A Pengaruh Peran Suami terhadap Imunisasi Dasar Lengkap Pada Anak Di Desa Kayu Bawang Wilayah Kerja Puskesmas Gambut Tahun 2017 - Ni wayan Kurnia Widya Wati; Wulan Suci (HB PRESS, 2019)
During the preliminary study in the Village of Kayu Bawang, the results of immunization data were as many as 52 people (88,1%), BCG/Polio 1 as many as 54 people (54,5%), PENT1/Polio 2 as many as 54 people (91,5%), PENT2/Polio 3 as many as 46 people (8%), PENT3/Polio 4 as many as 50 people (84,7%), and Measles as many as 46 people (78,0%). The purpose of this study was to determine the effect of husband’s role on complete basic immunization in children in the Village of Kayu Bawang Working Area of Gambut Public Health Center. The method used is analytical with cross sectional design. The subjects of this study were all husbands with children aged 9-12 months in the Village of Kayu Bawang Working Area of Gambut Public Health Center as many as 113 people. The sample in this study were 53 people taken with Random Sampling technique. The result of research can be concluded that the value of Sig. p = 0,002 <α (0,05) Ha is accepted, which means that there is a relationship between the influence of the husband’s role on complete basic immunization of the children in Kayu Bawang Villagesin the Woking Areas of Puskesmas Gambut in 2017. It is suggested to the Puskesmas officers to do extension about the importance of husband role to immunization in children.